2009
DOI: 10.1556/aphysiol.96.2009.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of attending elevated level school physical education in 7 to 11-year-old boys

Abstract: The aim of the present longitudinal study of four years was to analyse differences in growth patterns, age-related changes in body fat and physical performance in schoolchildren taking part either in normal or in elevated level physical education at school.Nine data collection sessions were carried out between 2002 and 2006 in 18 schools. The sample consisted of 521 non-athletic volunteer boys (PE=116, contrast = 405).The inter-group differences between mean height, body weight, body mass index, relative body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The 2 dietary behavior interventions did not have a significant effect on mean BMI (50,51). All PA studies, except for one (55), found a significant effect on BMI or BMI z score for the overall sample (59,60) or for girls (56,57). No ES could be calculated for these studies.…”
Section: Bmimentioning
confidence: 91%
See 4 more Smart Citations
“…The 2 dietary behavior interventions did not have a significant effect on mean BMI (50,51). All PA studies, except for one (55), found a significant effect on BMI or BMI z score for the overall sample (59,60) or for girls (56,57). No ES could be calculated for these studies.…”
Section: Bmimentioning
confidence: 91%
“…With regard to the PA interventions only, those measuring physical fitness (n = 3) as an outcome showed a significant increase in performance on most fitness indicators (52,54,59). Of those interventions evaluating time spent being physically active (n = 4), all but one (58) found a significant increase in the intervention group (47,53,56,57).…”
Section: Pa Behaviormentioning
confidence: 99%
See 3 more Smart Citations